Properties of a mutant of Streptococcus mutans altered in glucosyltransferase activity. - Kuramitsu, H K (1976)
A mutant of Streptococcus mutans GS-5 has been isolated as a smooth colonial variant on mitis salivarius agar. This mutant, designated SNG-1, adheres to glass surfaces as well as the parental organism when grown in the presence of sucrose. However, in contrast to the parental organism, glucose-grown cultures of the mutant did not adhere to smooth surfaces when incubated with sucrose under nongrowing conditions. The inability of the mutant organism to adhere to glass surfaces under the latter condition was a result to markedly reduced levels of mutant cell-associated glucosyltransferase activity. In addition, the extracellular activity of the mutant was also severely depressed relative to the parental activity. The reduced levels of mutant enzyme activity appear to be a result of a mutation in a structural gene coding for glucosyltransferase activity since (i) mutant glucosyltransferase activity is much less resistant to heat inactivation compared to the parental enzymes and (ii) the migration patterns of the mutant and parental enzymes differ on polyacrylamide gels and after isoelectric focusing on polyacrylamide gels. However, the kinetic properties of the mutant enzymes are similar to those of the comparable parental activities in terms of pH and temperature optima and Km values for sucrose. The mutant enzyme responsible for soluble glucan synthesis has been purified approximately 300-fold. These results are discussed in terms of the mechanism of glucan synthesis by S. mutans.